PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM MENGGUNAKAN MEDIA PEMBELAJARAN REALIA DI SDN 04 BENGKAYANG - Devi Saputri, Silvester (CV. ADIBA ASIHA AMIRA, 2024)
This research aims to improve the motivation and learning outcomes of grade V students in Natural Sciences (IPA) through reality learning media at SDN 04 Bengkayang. The method used is school action research (PTK) which is carried out in two stages, each consisting of planning, action, observation and reflection. The subjects of the study were 35 students, 19 women and 16 men, namely students of class V.B. The results of the study show that the use of realia learning media can improve student learning outcomes by increasing student participation and enthusiasm in the learning process. In addition, student learning outcomes have also experienced a significant increase, as evidenced by the increase in student learning outcomes in the above science subjects (KKM). This study concludes that realia learning media is effective in improving the motivation and learning outcomes of grade V students of SDN 04 Bengkayang. Therefore, it is recommended that teachers integrate realia learning media into the learning process to achieve better results.